Legal Discovery in Islamic Perspective - Shabika Azzaria Putri; Labitha Cetizta Irwanti; Ari Rahmat Elsad (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
In general, legal discovery refers to conducting legal searches when the statutory regulations are not regulated and are unclear. Legal discovery is not only based on the concept of positive law, but it also refers to Islamic concepts. This aims to find the law on an issue where the regulation is not yet regulated. Thus, inexistence and unclear issues in law become present and apparent. Legal discovery in Islamic concept is known as Ijtihad, an act and an effort to find, understand, and formulate Islamic Shari’ah ruling. Legal discovery in Islam is conducted using several methods including istinbat, interpretation, literal/linguistic, causation (ta’lili), and synchronization methodologies. Other methods of legal discovery are qiyas, istihsan, maslahah mursalah, istishhab, urf, mazhab shahabi which cannot be separated from the main sources of Islamic law, the Qur’an and hadith. Meanwhile, ra'yu and ijtihad are ways of thinking in understanding the Qur’an and hadith. These are to determine a problem where its nash has not been determined. The researchers employed library research in this study. The study examined the documents using secondary data and analyzed it using a qualitative method where the data are described in words, not numbers. In addition, the data collection is based on literature studies taken from books, journals, and internet sources related to legal discovery in the Islamic concept.